Collection and in vitro maturation of Mazama gouazoubira (brown brocket deer) oocytes obtained after ovarian stimulation - Rola, Luciana Diniz [UNESP]; Zanetti, Eveline Dos Santos [UNESP]; Del Collado, Maite; Peroni, Ellen De Fátima Carvalho [UNESP]; Duarte, José Maurício Barbanti [UNESP] (Cambridge University Press (CUP), 2020)
Summary In vitro production of embryos has gained prominence as a tool for use in wildlife conservation programmes in situ and ex situ. However, the development of this technique depends on steps that include ovarian stimulation, collection and oocyte maturation. The purpose of this study was to assess the feasibility of an ovarian stimulation protocol for follicular aspiration, the efficiency of videolaparoscopy for follicular aspiration and test a medium for in vitro oocyte maturation for the species Mazama gouazoubira. Five females were submitted to repeated ovarian stimulation (hormone protocol using controlled internal drug release), and estradiol benzoate on D0 and eight injections of follicle-stimulating hormone, once every 12 h, from D4 onwards at 30-day intervals. Fourteen surgical procedures were performed in superstimulated females, resulting in the collection of 94 oocytes and an average of 17.1 ± 9.1 follicles observed, 13.5 ± 6.6 follicles aspirated and 7.2 ± 3.7 oocytes collected per surgery. After collection, the oocytes were submitted to in vitro maturation for 24 h and stained with Hoechst 33342 dye to evaluate their nuclear status; 64.5% of the oocytes reached MII and 16.1% were spontaneously activated by parthenogenesis. The nuclear status of oocytes that did not undergo in vitro maturation was evaluated; 80.9% were found to be immature.
Keywords: Assisted reproductive technologies; Deer; FSH; Keywords:; Laparoscopic ovum pick-up; Wild animals